2021
DOI: 10.3390/agronomy11091809
|View full text |Cite
|
Sign up to set email alerts
|

Using Remote Sensing and an Unmanned Aerial System for Weed Management in Agricultural Crops: A Review

Abstract: Weeds are unwanted plants that can reduce crop yields by competing for water, nutrients, light, space, and carbon dioxide, which need to be controlled to meet future food production requirements. The integration of drones, artificial intelligence, and various sensors, which include hyperspectral, multi-spectral, and RGB (red-green-blue), ensure the possibility of a better outcome in managing weed problems. Most of the major or minor challenges caused by weed infestation can be faced by implementing remote sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 68 publications
(61 citation statements)
references
References 97 publications
(124 reference statements)
1
42
0
Order By: Relevance
“…In computer vision, images with medium and high accuracy have become the data types commonly used by researchers, especially in species identification and classification in agriculture, such as agricultural vegetation classification, land use classification, crop classification, tree species identification, etc., ( Roslim et al, 2021 ; Chen Z. et al, 2021 ; Li et al, 2021 ; Yan et al, 2021 ). To solve the common problems of zoom sensing image segmentation algorithms, such as poor robustness, easy loss of edge information and narrow scope of application, the core task of zoom sensing image target detection is to judge whether there is a target in zoom sensing images and to detect, segment, extract and classify it.…”
Section: Related Workmentioning
confidence: 99%
“…In computer vision, images with medium and high accuracy have become the data types commonly used by researchers, especially in species identification and classification in agriculture, such as agricultural vegetation classification, land use classification, crop classification, tree species identification, etc., ( Roslim et al, 2021 ; Chen Z. et al, 2021 ; Li et al, 2021 ; Yan et al, 2021 ). To solve the common problems of zoom sensing image segmentation algorithms, such as poor robustness, easy loss of edge information and narrow scope of application, the core task of zoom sensing image target detection is to judge whether there is a target in zoom sensing images and to detect, segment, extract and classify it.…”
Section: Related Workmentioning
confidence: 99%
“…These UAVs can also be equipped with multispectral cameras, which provide more information than an RGB digital image because they record spectral bands not visible to the human eye, such as near infrared (NIR), and provide data on things such as visible light reflectance and vegetation indices [15]. Multispectral imaging initiated by sensors compute reflected energy within several specific sections or are recognized as bands of the electromagnetic spectrum and utilized about tens of discrete spectral bands for image processing [17]. This multispectral image can be taken from a UAV at usually 60 and 70 m height, depending on the type of crops and location [18].…”
Section: Unmanned Aerial Vehicle (Uav) and Weed Detection Using Multi...mentioning
confidence: 99%
“…al. [80] found that the artificial intelligent (AI) can be used to detect the weeds patches in the rice field. Thus, the used of UAV can help to gain the highest spatial and spectral resolution in the field.…”
Section: Effect Of Spatial and Spectral Resolutions On Weed Detectionmentioning
confidence: 99%